Entrepreneur magazine's ultimate book of sales letters : customize your letters, memos, E-Mails and presentations with the enclosed CD-ROM - Kimball, Cheryl ([Irvine, Calif.], Entrepreneur Press, 2007)
With 1.001 sample documents, this book goes beyond typical sales templates; it offers communication customized specifically for you. It details how to use a complete letter-oriented strategy, covering a variety of communication types, topics, and approaches to selling
1. Basics of selling -- 2. Letters for prospecting -- 3. Letters for sales operation
magazine, Entrepreneur
Keywords: COMMERCIAL CORRESPONDENCE